Influence of adding a commercial phytosterol ester mixture on the 'equilibrium' crystallization behavior of palm oil. (July 2018) - Daels, Eva; Goderis, Bart; Steen, Liselot; Foubert, Imogen
Graphical abstract: Highlights: Low phytosterol ester (PE) concentration: dilution effect. High PE concentration: PEs crystallized in 1 or 2 crystal forms. Addition of PEs led to a decrease in melting enthalpy and hardness of palm oil. Binary system showed eutectic characteristics. Abstract: The objective of this study was to in depth investigate the 'equilibrium' state morphology and properties of crystals obtained after long-term isothermal crystallization and annealing of palm oil (PO) in the presence of different concentrations of phytosterol esters (PEs). A commercially available mixture of PEs was added to PO (0–100% PEs, 10% increment) and the effect of PE addition was analyzed with differential scanning calorimetry, X-ray diffraction, nuclear magnetic resonance, polarized light microscopy and texture analysis. It was observed that PE addition had a major influence on each level of the crystalline structural hierarchy of PO in the 'equilibrium' state. The PE-PO binary system showed eutectic behavior. In case of a low PE concentration PEs itself did not crystallize but acted as a liquid oil diluting PO, while when added in a high concentration, PEs crystallized separately from PO. From a concentration of 40% PEs next to the β' crystals of PO also PEx crystals were observed in the blends and from a concentration of 80% PEs additionally also the PEy liquid crystals were formed. The amount of PEy in the blends with 80% and 90% PEs was however too low for the formation of the dense crystal structure as seen in pure PE. The crystal network structure of pure PO was lost after PE addition leading to a drop in the hardness.